Development of the Weight-Related Sign and Symptom Measure - Meryl Brod; Lise Højbjerre; Kathryn M. Pfeiffer; Robyn Sayner; Henrik H. Meincke; Donald L. Patrick (SpringerOpen, 2018)
Abstract Background Overweight and obesity have been associated with physical and emotional signs & symptoms. Research has shown that modest weight loss can mitigate some symptoms in individuals with overweight or obesity. This study's purpose was to conduct concept elicitation (CE) interviews to provide documented qualitative support for the development of the Weight-Related Sign and Symptom Measure (WRSSM) to assess weight-related signs/symptoms in U.S. adults with overweight or obesity, with or without type 2 diabetes (T2DM). Eight focus groups were conducted in the U.S. with adults with overweight or obesity to understand weight-related sign/symptom impact from the patient perspective. Individual interviews were conducted with clinical experts to understand the impact of overweight or obesity on patient signs and symptoms. Transcripts were analyzed to identify symptoms and observable signs. A clinical challenge was conducted with clinical experts to confirm the signs/symptoms were clinically relevant, important to patients, and would improve with modest weight loss. Cognitive debriefing (CD) was conducted with individuals with overweight or obesity to confirm readability and symptom relevance. Results CE interviews were conducted with four clinical experts, and 61 people, 32% of whom had T2DM, participated in the focus groups. Analyses identified two major areas of obesity impacts: weight-related physical signs/symptoms, and emotional impacts. The most frequently reported physical signs/symptoms were feeling tired (74%), shortness of breath (69%), and joint pain (64%). The most often reported emotional impacts included poor self-image (72%) and depression (51%). Twelve signs/symptoms were identified during item generation and included on the preliminary measure. Twelve adults with overweight/obesity, who were not part of the focus groups, participated in CD. After the CD, a validation-ready, 10-item WRSSM measure was generated. Conclusions Findings provide evidence of content validity for the validation-ready WRSSM in U.S. adults with overweight or obesity, including people with and without T2DM.